THE INFLUENCE OF SOWING SCHEMES AND RATES OF BIOSTIMULITATORS ON THE BIOMETRIC INDICATORS OF FODDER ROOT BEET VARIETY “UZBEKISTAN-83” - Yuldasheva Zulfiya Kamalovna; Mamatdurdiev Ulugbek Firnafas ugli (GLOBAL SCIENTIFIC RESEARCH AND INTELLECTUAL PURSUITS, 2026)
This article studies the effect of sowing schemes and biostimulant rates on biometric indicators of root-fruits of the Uzbek-83 variety of fodder beet. In the experiment, three sowing schemes of 70x15, 70x20, 70x25 were used, and the Tandem biostimulant was applied in three different rates, before sowing, seed treatment and foliar feeding twice during the growing season. The Fitovak biostimulant was used as a standard for this biostimulant. It was observed that the variant using the Tandem biostimulant in the rate of 0.4 + 0.7 + 0.9 was better.